Environmental regulation and food safety : studies of protection and protectionism - Jha, Veena, 1959- (Edward Elgar ; IDRC, 2006)
Environmental, health and sanitary requirements in developed countries are perceived in developing countries as non-tariff barriers to trade. This book shows that such restrictions are perceived to be more stringent during the domestic production season. It also argues that scientific data for specific thresholds appear to be questionable.